PEMANFAATAN INOKULAN MIKROBA SEBAGAI PENGKAYA KOMPOS PADA BUDIDAYA SAYURAN - Sarjiya Antonius; Maman Rahmansyah; Dwi Agustiyani Muslichah (Research Center for Biology-Indonesian Institute of Sciences, 2015)
Microbial existence is due to mineralize organic compound in soil and caused nutrients availability to the plants. In this study, some of microbial inoculants consist of a). Phosphate soluble bacteria (Pseudomonas sp.) collected from soils that intensively utilized agrochemical in its agriculture activities; b). Nitrogen - fixing bacteria Rhizobium leguminosarum; and c) Trichoderma sp. and Aspergillus sp.as organic degradation fungi were used for compost enrichment.These inoculants formulation were utilized to carrots (Daucus carota L.), broccoli (Brassica oleracea L.) and maize (Zea mays L.) cultivation in upland area, Cisarua, Bogor, West Java. This study was aimed to assess inoculants response to enrich fully mature and half ripe compost. Crops response to the inoculation treatment was varied among these commodities. In general, the response of plants with the use of compost enriched biofertilizer was positive, with an increase in yield of about 15- 30% for carrots, broccoli around 65- 90% and about 10% of corn crops. The significant increase in crops production as impact of organic fertilizier application indicated that C organic content of the organic farm of Cimelati and Agato were defisit.